Respuesta :
Answer:
[tex] \large \sf \: 6y - 8[/tex]
Step-by-step explanation:
Let's simplify step-by-step.
8y−2(y+4)
Distribute:
=8y+(−2)(y)+(−2)(4)
=8y+−2y+−8
Combine Like Terms:
=8y+−2y+−8
=(8y+−2y)+(−8)
=6y+−8
=6y−8
Answer:
6y - 8
Step-by-step explanation:
This is a simplifying problem, so we just need to separate and link the like terms.
First we start with the parenthesis by distributing
-2*y + -2*4
-2y - 8
We can the put it back into the equation
8y - 2y + 8
8y and -2y are like terms so we can put them together to get 6y
6y +8